Selective arylation of 2-bromo-4-chlorophenyl-2-bromobutanoate via a pd-catalyzed suzuki cross-coupling reaction and its electronic and non-linear optical (NLO) properties via dft studies - Nazeer, Usman; Rasool, Nasir; Aqsa, Mujahid; Mansha, Asim; Muhammad Zubair, Abdul Wahab Saaroni; Kosar, Naveen; Mahmood, Tariq; Ali Raza, Shah; Syed Adnan, Ali Shah; Zainul Amiruddin, Zakaria; Muhammad Nadeem, Akhtar (MDPI - Open Access Publishing, 2020)
In the present study, 2-bromo-4-chlorophenyl-2-bromobutanoate (3) was synthesized via the reaction of 2-bromo-4-chlorophenol with 2-bromobutanoyl bromide in the presence of pyridine. A variety of 2-bromo-4-chlorophenyl-2-bromobutanoate derivatives (5a–f) were synthesized with moderate to good yields via a Pd-catalyzed Suzuki cross-coupling reaction. To find out the reactivity and electronic properties of the compounds, Frontier molecular orbital analysis, non-linear optical properties, and molecular electrostatic potential studies were performed.